Development of a Laboratory-based Physics Module with a Science Process Skills Approach to enhance the interest of High School Students - Abdul Hamid; Ainal Mardiah; Agus Wahyuni; Elisa Kasli; Sri Wahyuni; Ngadimin Ngadimin; Zainuddin Zainuddin (Asian Journal of Science Education, 2023)
This study aims to develop a laboratory work-based physics module with a Science Process Skills approach to increase the interest of high school students. The research model used was ADDIE development and the research design used was research and development. The subjects in this study were 2 physics teachers and 20 class X students at SMA Negeri 1 Meulaboh. Research data was obtained through expert lecturer validation sheets, teacher and student response questionnaires. The feasibility of the module is measured by the validation of expert lecturers and questionnaire responses by research subjects. The overall result of the module validation shows a score of 95.07% which falls into the very feasible category, the teacher's response is 79% and the student's response is 74.5%. Data processing was carried out through statistical analysis using a Likert scale. The validation results show that the module is suitable for use and the teacher and student response questionnaires show the subject's response is to agree. From the two measurements, it was found that the Laboratory Work-based Physics Module with the Science Process Skills approach could increase the interest of high school students.